HYBRID WAR AS AN ELEMENT OF BUILDING OF A NEW GEOPOLITICAL REALITY - Набока, А. В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2018)
The concept of hybrid war and methodological approaches to that concept are analyzed, similar means of political struggle of subjects of geopolitical confrontation during the 20th century are explored. Particular attention is paid to the peculiarities of the formation of a new world order in the era of globalization, the notion of «asymmetry conflicts» as one of the elements of a hybrid war is highlighted, and the existing system of international relations as partially operating is considered, diplomatic means, world order.